DOSES CRESCENTES DE BIOFERTILIZANTE NO DESENVOLVIMENTO DE MUDAS DE SCHIZOLOBIUM AMAZONICUM - LOPES, Mona Carolina Ribeiro; SILVA, Hebert Lizardo Germano; CORREA, Jonas de Sousa; WOICIECHOWSKI, Thiago (ANAIS DO ENIC, 2020)
-